2020
DOI: 10.1055/s-0040-1715153
|View full text |Cite
|
Sign up to set email alerts
|

Propeller Flaps in the Upper Extremity: Arm and Forearm Reconstruction

Abstract: The propeller flap is an island of skin that is raised on its pedicle (most commonly a single perforator) and can rotate 180 degrees to cover a soft tissue defect. Thanks to these features, the propeller flap brings reliable tissue from outside of the zone of injury while sparing the main vessels of the upper extremity. This technique limits the donor site to the same limb, captures skin characterized by having the same color and texture, does not necessarily need a microvascular anastomosis, and overall reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This research gap may be due to the challenge that upper extremity reconstruction results in shorter pedicle lengths in comparison to the lower extremity, and thus they are less utilized. 35 A systematic review and metaanalysis of 428 perforator-pedicled propeller flaps in lower extremity defects by Bekara et al reported a complication rate of 25.2% (n ¼ 108) and flap survival rate of 84.3% (n ¼ 361). 36 It appears PPFs used in upper extremity reconstruction have overall lower complication rates and better survival as seen in our findings and those of Lazzeri et al 9 When compared with reports on PPFs of the upper extremity more broadly, hand and digital PPFs appear to have a slightly higher complication rate and flap failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…This research gap may be due to the challenge that upper extremity reconstruction results in shorter pedicle lengths in comparison to the lower extremity, and thus they are less utilized. 35 A systematic review and metaanalysis of 428 perforator-pedicled propeller flaps in lower extremity defects by Bekara et al reported a complication rate of 25.2% (n ¼ 108) and flap survival rate of 84.3% (n ¼ 361). 36 It appears PPFs used in upper extremity reconstruction have overall lower complication rates and better survival as seen in our findings and those of Lazzeri et al 9 When compared with reports on PPFs of the upper extremity more broadly, hand and digital PPFs appear to have a slightly higher complication rate and flap failure rate.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Inoue and Taylor, 10 it is safer to include perforators from a radial and ulnar recurrent artery to stabilize blood flow near the cubital fossa. To do so, we included superficial flexor muscles to the flap, and it is possible to easily incorporate musculocutaneous perforators of ulnar and radial arteries 10–13 …”
Section: Discussionmentioning
confidence: 99%
“…To do so, we included superficial flexor muscles to the flap, and it is possible to easily incorporate musculocutaneous perforators of ulnar and radial arteries. [10][11][12][13] Some have also suggested that the postoperative contour of the shoulder is better to fit a prosthesis if the flap has a volume of flexor muscle groups. 2,14 Concerning the size of the flap that can be harvested, Kimura et al 11 reported that the average length of the forearm from the volar aspect of the pisiform bone to the medial epicondyle of the humerus was 22.8 cm.…”
Section: Discussionmentioning
confidence: 99%
“…A perforator-pedicled propeller flap (PPPF) is a versatile technique with many benefits, such as adequate blood supply, like-with-like repair, minimal donor site morbidity, and no extra intraoperative patient's position alteration (4)(5)(6). Given the abundance of musculocutaneous perforators for the overlying skin in trunks and extremities, PPPFs serve as a primary workhorse for treating the defects caused by wide resection of tumors in these regions (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%